Medium-term and top-down budgeting in OECD countries - Moretti, Delphine (OECD Publishing, 2023)
This paper, based on preliminary results of the 2023 OECD SBO Survey on Budget Frameworks, takes stock of OECD countries' practices in top-down and medium-term budgeting. It shows that OECD countries' fiscal frameworks can be characterised by strong reliance on multiple fiscal rules or objectives for enforcing fiscal discipline, with medium-term and top-down budgeting not used yet to their full potential in some countries. Drawing on the OECD Spending Better Framework, this paper advises that countries that wish to strengthen their fiscal frameworks reinforce the processes and institutions that underpin effective medium-term and top-down budgeting systems. Central to this is producing and publishing more regularly baseline projections of government expenditures and setting credible multi-year expenditure ceilings that serve as stringent guidelines for budget planning, while also allowing for some degree of flexibility under clearly defined conditions